PERAN STRATEGIS ROOM DIVISION DALAM MENINGKATKAN KUALITAS PELAYANAN DI ARTE HOTEL MALIOBORO - Rakhmat Sarwo Adi; Kris Cahyani Ermawati; Darmaesti (Universitas Pendidikan Ganesha, 2026)
The Room Division plays a crucial role in hotel operations. It comprises the Front Office and Housekeeping departments, which work together to ensure the quality of service and overall efficiency of hotel operations. At Arte Hotel Malioboro, the Room Division plays a strategic role in supporting operations and enhancing guest comfort. This study aims to determine how the Room Division plays a role in providing excellent service, managing occupancy rates, increasing sales, and enhancing hotel competitiveness. A qualitative descriptive method was used to examine hotel operations and relevant hotel management theories. Data were obtained through several methods, including observation, interviews with the Room Division Coordinator, Housekeeping Supervisor, Front Office employees, Housekeeping employees, guests, and document analysis. The results indicate that the Room Division is crucial in providing service to guests. This division also ensures smooth communication between departments. The Room Division plays a strategic role in Arte Hotel Malioboro's operations, which prioritize revenue from room sales. Hotel services remain optimal and competitive through coordination, employee training, and standardized service. The Room Division's strategic role not only focuses on operational services but also influences guest comfort and the hotel's ability to compete in the hospitality industry.